A multi-criteria analytical hierarchy process framework for the design of Türkiye's transcontinental hydrogen pipeline corridor - Celikdemir, Soner; Celikdemir, Meltem Yavuz; Ozdemir, Mahmut Temel (Pergamon-Elsevier Science Ltd, 2025)
This study presents a comprehensive and analytically robust framework for the design of a multi-stage Hydrogen Pipeline Corridor to facilitate the intercontinental transfer of green hydrogen from energy-rich Asia to Europe, where energy demand is steadily increasing. Within the context of multi-criteria decision-making, the Analytical Hierarchy Process was employed to evaluate four main criteria: energy production potential, energy consumption potential, renewable energy capacity, and industrial development combined with population density. The respective weights of these criteria were calculated as 55 %, 25 %, 6 %, and 14 %. Regional priorities were established, and statistical robustness was ensured through bootstrap analysis, yielding 95 % confidence intervals for regional scores and revealing significant differences among regions. The interconnections and relative contributions of cities were visualized using a Sankey diagram, providing a holistic view of supply-demand dynamics. Scenario-based cost-benefit and cost-performance analyses indicate that, under optimistic assumptions, the benefit/cost ratios reach 0.53 for the primary corridor, 0.64 for the secondary corridor, and 0.54 for the tertiary corridor. By replacing fossil-based hydrogen flows with green hydrogen, the proposed HPC has the potential to abate approximately 5 tCO2 per tonne of hydrogen transported, contributing significantly to Europe's decarbonization efforts. Furthermore, the corridor is projected to generate annual revenues up to 1.8 billion under optimistic scenarios, enhancing supply diversification and leveraging T & uuml;rkiye's unique transcontinental position as a strategic energy bridge. These findings offer actionable insights for policymakers and investors, supporting the feasibility and scalability of large-scale hydrogen infrastructure planning in T & uuml;rkiye and the broader region.
Keywords: Hydrogen pipeline corridor; Analytical Hierarchy Process; Energy corridor estimation; Bootstrap analysis